Using Digital Concept Maps to Distinguish Between Young Refugees' Challenges. Issue 1 (5th April 2017) - Brooker, Abi; Lawrence, Jeanette; Dodds, Agnes
Digital media are beneficial for research of complex refugee issues, as they allow refugees to express their personal experiences of complex issues in ways that are not restricted by language barriers or limited in authenticity, while also offering researchers a way to systematically compare refugees' varied experiences. We used a computerised concept mapping task to ask 74 young refugees (teenagers and young adults), from three separately recruited samples, to think about their experiences with various challenges they might face during settlement, distinguishing between their challenges in terms of size. Our analyses focused on one major challenge in Australia, learning the English language, and how it related to ten other challenges of resettlement. The three samples differed in educational setting, cultural background, age, and time in Australia. These refugees faced multiple challenges in their lives. Regardless of differences between the groups, the 74 shared a single pattern of experiences in which English language was substantially bigger, and more frequently endorsed, than other challenges. The three samples differed in how they described their experiences with their English language challenges. Our findings suggest a need for more support learning the English language, even for those who might be assumed to have good levels of conversational or academic English. This support needs to extend beyond the 510 hours of support received upon arrival in the country. Findings also suggest that such support could help young refugees overcome other challenges as they settle in Australia, especially in their academic, social, and employment experiences.